Do regular exercise, gender, and age influence smartphone addiction? Analyzing screen time and smartphone deprivation symptoms - Pirwani, Neha; Somogyi, Angéla; Szabo, Attila (Frontiers in Psychology, 2025)
BackgroundHeadless smartphone use, known as smartphone addiction (SA), is associated with mental health issues and behavioral dependencies. While physical activity (PA) has been suggested as a protective factor, research remains inconclusive. The present study examines whether regular exercise influences SA, smartphone deprivation, and daily smartphone screen time while assessing gender and age as risk factors.MethodsThis cross-sectional study with 701 participants (392 exercisers, 309 non-exercisers) assessed SA with the Smartphone Application-Based Addiction Scale (SABAS) and deprivation feelings with the Hungarian Smartphone Withdrawal Symptom Scale (HSWSS). Daily smartphone use was self-reported. Multivariate analysis of covariance examined the effects of exercise status, gender, and age on SA-related variables.ResultsExercise status did not significantly affect SA, deprivation feelings, or screen time (p > 0.05). However, the correlation between SA and smartphone screen time was stronger (p < 0.05) in non-exercisers (r = 0.407) than in exercisers (r = 0.274). Gender and age were significant predictors: females reported higher SA and usage, and younger age was associated with greater SA, deprivation symptoms, and more screen time.ConclusionWhile exercise may not reduce SA, exercisers exhibit a weaker link between SA and smartphone use, suggesting less problematic usage, possibly due to more utilitarian (e.g., sports-related) rather than hedonic use. Females report higher SA, feelings of deprivation, and screen time than males, while age correlates with increased SA, feelings of deprivation, and screen time. Future research should examine psychosocial mechanisms and diverse smartphone usage patterns in addiction in connection with exercise behavior.